Evaluating the effects of catch-and-release angling on Cape stumpnose Rhabdosargus holubi in a South African estuary. Issue 3 (3rd July 2018) - Arkert, NK; Childs, A-R; Parkinson, MC; Winkler, AC; Butler, E; Mannheim, S; Potts, WM
Abstract : Fisheries managers are increasingly promoting catch-and-release (C&R) to manage recreationally angled fish stocks. Despite this, there is a scarcity of information on the effects of C&R on estuarine-dependent species. Cape stumpnose Rhabdosargus holubi dominates the recreational fisheries catch and provides an important source of food for subsistence fishers in some temperate South African estuaries. The health and survival of R. holubi exposed to a C&R event was investigated by examining their physiological stress response (blood glucose and lactate), reflex impairment (reflex action mortality predictors [RAMP]) and short-term (12-hour) survival. Fish were captured and exposed to one of three air-exposure treatments: 0 s, 30 s or 90 s. Stress and health were measured either immediately (immediate) or one hour after (delayed) the C&R event. There was no significant difference in blood glucose between air-exposure treatments, but there was a significant difference between the mean immediate and delayed glucose levels within each treatment ( F (2, 143) = 81.8, p < 0.01). In contrast, blood lactate level was significantly higher in the 90-s treatment ( p < 0.05). Immediate blood lactate levels were significantly lower than the delayed samples for each treatment ( F = 4.29, p = 0.02; n = 169). Although all fish exhibited at least one reflex impairment, the RAMP score was significantly higher in the 90-s air-exposure treatment ( H (2, 86) = 9.73, p = 0.007). Also, RAMP scores were significantly lower in the delayed samples ( p < 0.01). Although short-term mortality was relatively low (2.3%) for this species, it was highest in the 90-s treatment (7%). These results suggest that physiological stress is higher when R. holubi are exposed to longer periods of air exposure and that the physiological stress of fish subject to a C&R event is best measured after a delay.